THEORY AND ANALYSIS OF HUMAN CAPITAL (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the theory and analysis of human capital in the areas of economics, the emergence, formation, problems, economic category, management, development and dissemination of the modern concept of human capital.